THE DIAGNOSIS OF THE WHEELSET CONGESTION OF ELECTRIC ROLLING STOCK IN MOTION AND ITS IMPACT ON SUPERSTRUCTURE - Panchenko, O. O. (Science and Transport Progress, 2008)
The method of complex determination of locomotive weight and its dynamic effects on superstructure of railway track on the basis of automated measuring systems having no cargo platform devices is offered.